Optimum design of composite structures with ply drop-offs using response surface methodology. Issue 7 (26th January 2021) - Diniz, Camila Aparecida; Méndez, Yohan; de Almeida, Fabrício Alves; da Cunha Jr, Sebastião Simões; Gomes, G.F.
Abstract : Purpose: Many studies only take into account the ply stacking sequence as the design variable to determine the optimal ply drop-off location; however, it is necessary to optimize other parameters that have a direct influence on the ply drop-off site such as which plies should be dropped and in which longitudinal direction. That way, the purpose of this study is to find the most significant design variables relative to the drop-off location considering the transversal and longitudinal positions, seeking to achieve the optimal combination of ply drop-off locations that provides excellent performance for the laminate plate. Design/methodology/approach: This study aims to determine the optimal drop-off location in a laminate plate using the finite element method and an approach statistical with design of experiments (DOE). Findings: The optimization strategy using DOE revealed to be satisfactory for analyzing laminate structures with ply drop-offs, demonstrating that not all design factors influence the response variability. The failure criterion response variable revealed a poor fit, with an adjusted coefficient of determination lower than 60%, thus demonstrating that the response did not vary with the ply drop-off location. Already the strain and natural frequency response variables presented high significance. Finally, the optimization strategy revealed that the optimal drop-off location that minimizes the strain and maximizes the natural frequency is the ply drop-off located of the end plate. Originality/value: It was also noted that many researchers prefer evolutionary algorithms for optimizing composite structures with ply drop-offs, being scarce to the literature studies involving optimization strategies using response surface methodology. In addition, many studies only take into account the ply stacking sequence as the design variable to determine the optimal ply drop-off location; however, in this study, the authors investigated other important parameters that have direct influence on the ply drop-off site such as which plies should be dropped and in which longitudinal direction.